Clinical spectrum and treatment outcomes in variants of Guillain-Barré syndrome: a case series - M., Yashfeen; K., Mugundhan (International Journal of Research in Medical Sciences, 2024)
Guillain-Barré syndrome (GBS) is an autoimmune polyradiculoneuropathy that is acute, typically severe, and fulminant. GBS has an incidence of 0.81-1.89 (median 1.11) per 100,000 person-years, and men are slightly more susceptible to GBS than females. 70% of individuals acquire this acute flaccid paralysis condition within 1-4 weeks following a respiratory infection or diarrhoea (especially Campylobacter jejuni). There are several identified subtypes of GBS, with acute inflammatory demyelinating polyneuropathy (AIDP) being the most prevalent. Additionally, there are two "axonal" subtypes: acute motor axonal neuropathy (AMAN) and acute motor sensory axonal neuropathy (AMSAN), both of which are clinically severe. The clinical trial of ophthalmoplegia, ataxia, and areflexia characterizes a different subtype called Miller Fisher syndrome (MFS) linked to anti-GQ1b antibodies. The patient’s medical history, along with neurological, electrophysiological, and cerebrospinal fluid tests, are used to diagnose GBS. Intravenous immunoglobulin (IVIG) and plasma exchange are effective treatments; however, newer approaches are required because 25% of patients eventually need mechanical ventilation, 20% are unable to walk, and 2-5% of patients may experience relapses.